Simulation based evaluation of time-variant loadings acting on tunnel linings during mechanized tunnel construction - Ninic, Jelena; Meschke, Günther (Elsevier, 2017)
In the design of machine driven tunnels, the loadings acting on the segmental lining are often adopted according to simplified assumptions, which improperly reflect the actual loading on the linings developing during the construction of a bored tunnel. A coupled 3D Finite Element model of the tunnel advancement process including the ring-wise installation of the lining and the hardening process of the grouting material serves as the basis for the analysis of the actual spatiotemporal evolution of the loading on the lining during tunnel construction. The distribution of the loadings in the different construction phases is calculated using a modified surface-to-surface contact condition imposed between the solidifying grouting material in the tail gap and the lining elements. An extensive parametric study investigates the influence of the initial grouting pressure, the pressure gradient, the temporal stiffness evolution, the soil permeability as well as the interface conditions between the grouting material and the tunnel shell on the temporal evolution of the loading on linings.